ANALYZING EDUCATION TOWARD ENTREPRENEURIAL SUCCESS IN MANADO - Montolalu, Reity T.; Pandowo, Merinda H.Ch (Universitas Sam Ratulangi, 2018)
Abstract: Many people believe that educated people has a great potential to succeed in the future. As well as being an entrepreneurs, many people think that to become an entrepreneurs must have a basic knowledge (formal and informal education) that can be using to succeed in business. But knowadays level of education ever taken by entrepreneurial success of course difrrent. The objective of this study is to analyze how the role of formal and informal education and level of education toward entrepreneurial success in Manado. This research uses Qualitative Method with In-depth Interview, in order to knowÂ the role of formal and informal education and level of education toward entrepreneurial success in Manado. The result of this research is the role of formal and informal education and level of education is not the main factor or shows a weak relations toward entrepreneurial success in case culinary business in Manado. Based from the result gained, there are other factors that are more gives a big role toward the success of the business. From the result, the researcher recommended to next researcher to examine the other factors to analyze entrepreneurial success.Keywords: formal education and informal education, level of education, entrepreneurial success Â